Ataxia-associated DNA repair genes protect the Drosophila mushroom body and locomotor function against glutamate signaling-associated damage - Eidhof, Ilse; Krebbers, Alina; van de Warrenburg, Bart; Schenck, Annette (Frontiers in Neural Circuits, 2023)
The precise control of motor movements is of fundamental importance to all behaviors in the animal kingdom. Efficient motor behavior depends on dedicated neuronal circuitssuch as those in the cerebellumthat are controlled by extensive genetic programs. Autosomal recessive cerebellar ataxias (ARCAs) provide a valuable entry point into how interactions between genetic programs maintain cerebellar motor circuits.We previously identified a striking enrichment of DNA repair genes in ARCAs. How dysfunction of ARCA-associated DNA repair genes leads to preferential cerebellar dysfunction and impaired motor function is however unknown. The expression of ARCA DNA repair genes is not specific to the cerebellum. Only a limited number of animal models for DNA repair ARCAs exist, and, even for these, the interconnection between DNA repair defects, cerebellar circuit dysfunction, and motor behavior is barely established. We used Drosophila melanogaster to characterize the function of ARCA-associated DNA repair genes in the mushroom body (MB), a structure in the Drosophila central brain that shares structural features with the cerebellum.Here, we demonstrate that the MB is required for efficient startle-induced and spontaneous motor behaviors. Inhibition of synaptic transmission and loss-of-function of ARCA-associated DNA repair genes in the MB affected motor behavior in several assays. These motor deficits correlated with increased levels of MB DNA damage, MB Kenyon cell apoptosis and/or alterations in MB morphology. We further show that expression of genes involved in glutamate signaling pathways are highly, specifically, and persistently elevated in the postnatal human cerebellum. Manipulation of glutamate signaling in the MB induced motor defects, Kenyon cell DNA damage and apoptosis. Importantly, pharmacological reduction of glutamate signaling in the ARCA DNA repair models rescued the identified motor deficits, suggesting a role for aberrant glutamate signaling in ARCA-DNA repair disordersIn conclusion, our data highlight the importance of ARCA-associated DNA repair genes and glutamate signaling pathways to the cerebellum, the Drosophila MB and motor behavior. We propose that glutamate signaling may confer preferential cerebellar vulnerability in ARCA-associated DNA repair disorders. Targeting glutamate signaling could provide an exciting therapeutic entry point in this large group of so far untreatable disorders.